B/N-doped carbon sheets from a new ionic liquid with excellent sorption properties for methylene blue - Mehler, Julian; Ermer, Matthias; Paap, Ulrike; Heller, Bettina; Maier, Florian; Steinrück, Hans-Peter; Hartmann, Martin; Korte, Carsten; Schulz, Peter; Wasserscheid, Peter (Journal of Ionic Liquids, 2021)
The pyrolytic treatment of the novel ionic liquid 1-ethyl-3-methyl-imidazolium tetrakis-(1-imidazolyl)borate ([EMIM][BIm4]) allowed the preparation of B/N-doped carbonaceous materials with an exceptional performance in the adsorptive removal of the cationic dye methylene blue (MB) from wastewater. [EMIM][BIm4] was prepared via an easy and scalable synthesis protocol in very good yield. The carbon materials obtained after salt templated pyrolysis of the IL displayed high degrees of heteroatom doping (up to 22 wt% N, 3 wt% B) and high surface areas of up to 1860 m2 g−1. The materials were tested for their performance in the adsorptive removal of MB from contaminated water. Adsorption equilibrium experiments revealed an adsorption capacity exceeding 500 mg g−1, which is, to the best of our knowledge, the highest value reported so far. Time-resolved adsorption experiments showed that the materials not only exhibit high capacity but also very fast adsorption kinetics. Complete decolorization of MB solutions in only 5 min at high MB concentrations of 100 mg L−1 was observed. These results demonstrate that [EMIM][BIm4] is an excellent precursor for the preparation of IL-derived B/N-doped carbon sorbents.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Adsorption; B/N doped carbon nanosheets; Ionic liquid precursor; Material synthesis

In situ Raman and FTIR spectroscopic study on the formation of the isomers MIL-68(Al) and MIL-53(Al) - Embrechts, Heidemarie; Kriesten, Martin; Ermer, Matthias; Peukert, Wolfgang; Hartmann, Martin; Distaso, Monica (RSC Advances, 2020)
The topological metal-organic framework isomers MIL-53 and MIL-68 form from similar educts but differ in their pore geometries. They have been known for several years, but their synthesis is always reported separately. In consequence, the underlying mechanism and decisive synthesis parameters leading to the formation of either MIL-53 or MIL-68 are not understood. The present study shows how to induce the formation of MIL-68(Al) rather than MIL-53(Al) at low synthesis temperatures in N,N-dimethylformamide (DMF) using a modulated synthesis approach. MIL-68(Al) is identified as the intermediate product of formic acid modulated synthesis, which converts into the thermodynamically stable MIL-53(Al) product at longer synthesis times. The interactions of formic acid with the synthesis precursors responsible for inducing MIL-68(Al) formation are investigated with in situ Raman and FTIR spectroscopy. In contrast to the commonly assumed modulation mechanism of competitive coordination of linker and modulator with the metal node, formic acid is shown to form hydrogen bonds via the carboxylic group of the terephthalic acid (H2BDC) linker, slowing prenucleation building unit and subsequent crystal growth. MIL-68(Al) formation is favored by the combination of a deficiency of terephthalic acid in solution and a slow MOF growth rate. Dissolved H2BDC in solution is proposed to hinder MIL-68(Al) formation by serving as a molecular template for the rhombic MIL-53(Al) pore channels.
CRIS-Team Scopus Importer:2020-03-17

Perspective on the Use of Ultrasonic Monitoring for In Situ Diagnostics of Zeolite and MOF Crystallization - Ermer, Matthias; Reber, Rebecca; Baser, Hasan-Hüseyin; Fischer, Marcus; Schwieger, Wilhelm; Hartmann, Martin (Crystal Growth and Design, 2023)
The investigation and understanding of the underlying mechanisms for the crystallization of molecular sieve materials, such as metal-organic frameworks (MOFs) and zeolites, have received increasing interest in recent years. This is mainly because improvements of the corresponding equipment were made that are essential for in situ diagnostics. In contrast to classical techniques, such as X-ray diffraction and neutron scattering, nuclear magnetic resonance, or infrared and Raman spectroscopy, ultrasonic monitoring has not received proper attention. Thereby, especially for zeolites, important insights have been gained with this technique already. However, for MOFs, the number of publications dealing with in situ US monitoring is still limited. Therefore, this perspective gives an overview of the topic of in situ monitoring of crystallization of zeolites and MOFs and highlights the work that has been done so far by ultrasonic monitoring. Furthermore, we state benefits and current challenges for further establishing ultrasonic monitoring as a tool for the investigation of crystallization processes.
CRIS-Team Scopus Importer:2023-07-21

Role of Prenucleation Building Units in Determining Metal-Organic Framework MIL-53(Al) Morphology - Embrechts, Heidemarie; Kriesten, Martin; Ermer, Matthias; Peukert, Wolfgang; Hartmann, Martin; Distaso, Monica (Crystal Growth and Design, 2020)
While it is well-known that the particle size of solvothermally synthesized metal-organic frameworks (MOFs) can be controlled by tuning the solvent composition, which affects the solubility of the linker and metal salt educts, the exact relationship between linker solubility, initial chemical coordination steps occurring in solution, and the resulting MOFs' particle size has not yet been investigated. Here, we have studied the solvothermal synthesis of MIL-53(Al) in DMF and water/DMF mixtures with in situ Raman spectroscopy, which reveals the formation of intermediate prenucleation building unit (PNBU) species that consist of one linker molecule and one metal atom and self-assemble in solution to form MIL-53(Al). The concentration of PNBUs in solution prior to particle precipitation is dependent on the synthesis solvent ratio used and influences the MIL-53 particle size. Synthesis in pure DMF results in a high concentration of PNBUs in solution prior to MOF supersaturation and precipitation. This results in a large burst of MOF nucleation and the formation of nanosized MIL-53(Al) particles. Adding water to the DMF solution leads to reduced PNBU accumulation in solution prior to MOF precipitation due to the reduced linker solubility. The reduced accumulation of PNBUs prior to particle precipitation causes reduced nucleation and favors particle growth. The MIL-53(Al) particle size, in contrast, is independent of the MOF phase growth rate, which is highly dependent on the synthesis temperature.
CRIS-Team WoS Importer:2020-06-26

Synthesis of the novel MOF hcp UiO-66 employing ionic liquids as a linker precursor - Ermer, Matthias; Mehler, Julian; Kriesten, Martin; Avadhut, Yamini; Schulz, Peter; Hartmann, Martin (Dalton Transactions, 2018)
By using a terephthalate containing ionic liquid, a new metal-organic framework, hcp UiO-66, comprising (Zr12O8(OH)(14)) double clusters and terephthalate ligands has been synthesized. The hydrothermal synthesis of hcp UiO-66 might help to establish metal-organic frameworks for industrial scale applications.

UiO-66 and hcp UiO-66 Catalysts Synthesized from Ionic Liquids as Linker Precursors - Ermer, Matthias; Mehler, Julian; Rosenberger, Björn; Fischer, Marcus; Schulz, Peter; Hartmann, Martin (ChemistryOpen, 2020)
Using ionic liquids (ILs) as linker precursors, the well-known metal-organic framework (MOF) UiO-66 (Universitetet i Oslo) and the recently reported MOF hcp UiO-66 (hexagonal closed packed) have been successfully synthesized and characterized. The advantage of the applied novel synthesis approach is an economically and environmentally benign work-up procedure, due to the better solubility of the IL. Additionally, the reactivity of the terephthalate anions is increased compared to terephthalic acid, resulting in faster MOF formation with an increased amount of defects in the MOF structure. In order to explore to the influence of defects on the catalytic performance, the cyclisation of citronellal to isopulegol was employed as test reaction. The activity of hcp UiO-66 and fcc UiO-66 (face centered cubic) is improved compared to other MOF or zeolite based catalysts, while the selectivity is similar.
Keywords: UiO-66; metal-organic frameworks; ionic liquids; US damping; citronellal cyclization